Programma: 6 december Warren Harry; 7-8 december Bonga; 10 december Rachel Sweet; 12 december The Cure; 13 december Shusa & Band; 14 december Michael Chapman, Sail-Joia; 15 december The Flys; 16 december The Realists; 18 december Kevin Coyne (1979)
Programma: 6 december Warren Harry; 7-8 december Bonga; 10 december Rachel Sweet; 12 december The Cure; 13 december Shusa & Band; 14 december Michael Chapman, Sail-Joia; 15 december The Flys; 16 december The Realists; 18 december Kevin Coyne.